The ideational foundations of coercion: political culture and policies towards North Korea. Issue 2 (8th December 2015) - Onderco, Michal; Wagner, Wolfgang
Abstract : The notion that states' foreign and security policies are not exclusively driven by material interests is now firmly established. Whose ideas matter and in what way, however, has remained subject to debate. We advance this debate by studying the crisis diplomacy of liberal democracies towards North Korea during four crises around the country's violation of international norms between 1993 and 2009. Although liberal democracies share a common perception of North Korea's nuclear programme as a threat to international peace and security, they differ widely in either confronting or accommodating North Korea. We examine the explanatory power of two ideational driving forces behind the foreign policy of liberal democracies: the ideological orientation of the government, on the one hand, and a country's political culture, on the other. Our analysis of 22 liberal democracies demonstrates that different domestic cultures of dealing with norm violations have a significant impact on crisis diplomacy: countries with punitive domestic cultures tend to adopt confrontational policies towards international norm violators; while left governments are not more accommodationist than right governments. Ideational differences across states are thus more pronounced than those within states.